ANALISIS PENGARUH ECONOMIC VALUE ADDED DAN FAKTOR FUNDAMENTAL PERUSAHAAN TERHADAP HARGA SAHAM (STUDI KASUS PADA PERUSAHAAN YANG MASUK DALAM LQ45 BEI PERIODE 2006-2010) - , Bondan Christianddinata, ST. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Investing in the stock market is one way for investors to invest thier fund in order to get optimum gain. In taking their investment decisions, investors need various kinds of information about the objects they want to invest therefore they can maximize their investment profit in capital markets. The use of Economic Value Added (EVA) were claimed in previous studies as a better approach in explaining the stock price when compared with traditional performance analysis such as financial ratios, while on the other hand there are still studies that concluded the opposite. The purpose of this study is to analyze the influence of companyâs fundamental factors, such as EVA, Return On Assets (ROA), Return On Equity (ROE), and Earnings Per Share (EPS), to the company's stock price in the LQ45 index on the Indonesia Stock Exchange and to examines wether EVA is the best indicator to explain the stock price. This study uses data from corporate financial statements on a quarterly basis from 2006 until 2010. By using purposive sampling approach, we obtained samples of 40 companies resulting 800 observation data. The method used to analyze the influence of companyâs fundamental factors on the stock price is multiple linear regression using SPSS application version 17.00. The result form data analysis showed that EVA, ROA, ROE and EPS together have an influence on the company's stock prices in the LQ45 index on the Indonesian Stock Exchange amounting to 77.3% while the rest is explained by other factors not included in the present study. Partially, this study also shows that EVA have no influence on the company's stock prices in the LQ45 index on the Indonesian Stock Exchange, the same goes with ROA. ROE has significant negative effect on companyâs stock prices while the EPS has a dominant portion among other independent variables with a significant positive effect on companyâs stock prices included in the LQ45 index on the Indonesia Stock Exchange during 2006-2010 period.